2008
DOI: 10.1002/prca.200780058
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐shock protein‐27, ‐70 and peroxiredoxin–II show molecular chaperone function in sickle red cells: Evidence from transgenic sickle cell mouse model

Abstract: Sickle cell disease (SCD) is an autosomal recessive genetic red cell disorder characterized by the production of a defective form of hemoglobin, hemoglobin-S, that is worldwide-distributed. The acute clinical manifestations of SCD are related to hemoglobin cyclic-polymerization and to the generation of rigid, dense red blood cells (RBCs). We studied RBCs membrane proteome from human sickle RBCs, fractioned according to density compared to normal RBCs. 2-DE followed by MS analysis was carried out. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…Considering the high concentration of PRDX2 in RBC, the 5% is not negligible. It has further been shown that the level of PRDX2 association with the membrane is affected by oxidative stress [48,49] as well as hypoxia [50]. Membrane association of PRDX2 thought to involve the C- terminal region of PRDX2,has been shown to react with lipid hydroperoxides [33].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high concentration of PRDX2 in RBC, the 5% is not negligible. It has further been shown that the level of PRDX2 association with the membrane is affected by oxidative stress [48,49] as well as hypoxia [50]. Membrane association of PRDX2 thought to involve the C- terminal region of PRDX2,has been shown to react with lipid hydroperoxides [33].…”
Section: Discussionmentioning
confidence: 99%
“…Blood was centrifuged at 3000 g for 5 min at 4°C to remove plasma, passed through cotton to remove white cells, and washed three times with Ͷ choline wash solution (CWS: 155 mM choline, 1 mM MgCl 2 , 10 mM Tris-MOPS pH 7.4 at 4 °C, 290-300 mOsm) [15,16]. Packed red cells were lysed in phosphate lysis buffer (PLB: 5 mM Na 2 HPO 4 pH 8.0, added of a protease inhibitor cocktail tablet, 3 mM benzamidine, 1 mM Na 3 VO 4 final concentration) and washed in PLB 5 times to obtain almost white ghosts [17,18].…”
Section: Drugs and Chemicals Details Are Reported In Supplementary Mmentioning
confidence: 99%
“…In a mouse model for sickle cell disease characterized by abnormal activation of the Gardos channel, we have recently shown that the PRDX2 membrane association is modulated during hypoxia through an undefined mechanism [12]. The nature of association of PRDX2 to the red cell membrane is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Searches were not constrained by pI or molecular weight. 11,18 Peptide mixtures were also analyzed using microflow capillary liquid chromatography coupled with electrospray quadrupole time of flight tandem mass spectrometry (ESI Q-TOF MS/MS). ESI-MS/MS tandem spectra were recorded in the automated MS to MS/MS switching mode, with an m/z-dependent set of collision offset values.…”
Section: Protein Identificationmentioning
confidence: 99%
“…Cation transport activities were estimated according to previously published methods. 10,11 Briefly, the maximal rates of Na/K pump and Na/K/Cl co-transport activities were measured in cells containing equal amounts of Na + and K + (50 mmol/L of cells, obtained with the nystatin technique). With this procedure the internal sites for both transport systems were saturated.…”
Section: Red Cell Membrane Protein Analysismentioning
confidence: 99%